PENGARUH MODEL NUMBERED HEADS TOGETHER TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA MAN 2 PONTIANAK - Lestari, Puja; Hairida, Hairida; Rasmawan, Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to find out the differences between activities and learning outcomes between students who are taught using conventional model, as well as to find out the effects of Numbered Heads Together type cooperative learning model towards studentsâ€™ learning outcomes type hydrocarbon material of Class XI IPA in MAN 2 Pontianak. However, the form of research that the researcher uses is experimental research. The type of experimental research used is quasy-experimental design with nonequivalent control group design. The researcher sampling technique that is the Simple Random Sampling Technique, by drawing the class XI IPA 1which consists of 40 students as the control class, and class XI IPA 3 which consists of 40 students as the eperimental class. The result of the activity data anylisis using Mann-Whitney U test obtained Asymp.sig (2-tailed) in the amount of 0,000 (sig < 0.05). This shows that there are differences in learning outcomes between students who are given the NHT type cooperative learning model and those who are taught using convetional methods. The influence of NHT type cooperative learning model on student learning outcomes of Class XI IPA 2 Pontianak on hydrocarbon material resulted 12.55%, which is relatively low.Â Keywords: Numbered Heads Together Learning Model, Activity, Learning Outcomes, HydrocarbonÂ